Acetylcholinesterase Inhibition and Antioxidant Activity of N-trans-Caffeoyldopamine and N-trans-Feruloyldopamine - Muamer Dizdar; Danijela Vidic; Franc Požgan; Bogdan Štefane; Milka Maksimović (MDPI AG, 2018)
Phenolic acids and their derivatives found in nature are well-known for their potential biological activity. In this study, two amides derived from trans-caffeic/ferulic acid and dopamine were synthesized and characterized by Fourier-transform infrared spectroscopy (FTIR), mass spectrometry, proton and carbon-13 nuclear magnetic resonance spectroscopy. The compounds were tested for the inhibition of acetylcholinesterase (AChE) from Electrophorus electricus and for antioxidant activity by scavenging 2,2-diphenyl-1-pycrylhydrazyl free radical (DPPH•) and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) radical cation (ABTS•+), reducing ferric ions, and ferrous ions chelation. N-trans-Feruloyldopamine displayed the highest inhibitory effect on AChE with half-maximal inhibitory concentration (IC50) values of 8.52 μM. In addition, an in silico study was done to determine the most favorable AChE cluster with the synthesized compounds. Further, these clusters were investigated for binding positions at the lowest free binding energy. Both synthesized hydroxycinnamates were found to be better antioxidants than the parent acids in in vitro tests applied. N-trans-Caffeoyldopamine showed the best antioxidant activity in the three tested methods—against non-biological stable free radicals IC50 5.95 μM for DPPH•, 0.24 μM for the ABTS•+ method, and for reducing power (ascorbic acid equivalent (AAE) 822.45 μmol/mmol)—while for chelation activity against Fe2+ ions N-trans-feruloyldopamine had slightly better antioxidant activity (IC50 3.17 mM).